ANALISIS JUMLAH UANG BEREDAR DAN INFLASI TERHADAP NILAI AKTIVA BERSIH REKSADANA SYARIAH - Mitha Dwi Daka Etawati; Jeni Susyanti; Supriyanto Supriyanto (Reflektika, 2022)
Sharia mutual funds are viewed through the Net Asset Value or NAV. The NAV of Sharia Mutual Funds can be driven by factors from the money supply and inflation. Both of these factors are strong enough to increase the NAV of Islamic mutual funds. The purpose of this article is to analyze the effect of the money supply and inflation on the net asset value of Islamic mutual funds in 2017-2021. The results of the study stated that the variables of money supply (X1) and inflation (X2) together have a significant effect on the net asset value of Islamic mutual funds (Y), the variable money supply (X1) partially has a significant effect on the net asset value of Islamic mutual funds (Y). And the inflation variable (X2) partially affects the net asset value of Islamic mutual funds (Y)